The Development of Speaking Skills for Non-Native Speakers of English - Fatimah Azzahra; M. Ghufron Ghiffari Ghufron; Putri Meylani Erlan; Titania Putri Respati (English Instruction, 2020)
Speaking skills are viewed as motor-receptive and interaction skills in communication. As the rapid growth of technology, especially in the era of big data of Industrial Revolution 4.0, English speaking skills should be improved in order to be able to enhance communication with native speaker as well as non-native speakers in the international community. In the English as a Foreign Language (EFL) pedagogy environment, how to increase speaking competence and confidence for undergraduate students tends to be a crucial question among instructors. This concern led to a qualitative research design as an action study in a regular course employing a task-based approach. The findings indicated that confidence, creativity of topics, and speaking competence were the key aspects of improvement when speaking to the audience.